Description of New Host Record of Genus Hysterothylacium Ward and Magath, 1917 from Siluridae Catfish Wallago attu of Indus River Sindh, Pakistan: Short Communication: Catfishes Wallago attu in Sindh, Pakistan - Hira Soofi; Nadir Ali Birmani; Abdul Rasool Abbasi; Arifa Bhutto (Biological Sciences - PJSIR, 2022)
Current research on host catfishes Wallago attu collected from river Indus, Jamshoro, Sindh, Pakistan for examination of nematode parasites. Total of 27 specimens belong to genus Hysterothylacium was collected through the examination of nematode parasites, processes with slandered method of nematodes and identifies as Hysterothylacium carangis species was collected on the basis of diagnostic characteristics. Previously this species reported from intestine of fish Carangoides malabaricus of India but present species is new host record which is reported from catfish Wallgo attu of river Indus, Jamshoro, Sindh, Pakistan.